Diclofenac Induced Rapidly Progressive Renal Failure in Elderly Patient – A Case Report - C, Chandana; Anusha, Srirangam; B, Kavya H (Journal of Pharmacy Practice and Community Medicine)
(RPRF) Rapidly progressive renal failure is categorized by a rapid loss of kidney functions over days to weeks. Acute kidney injury is a sudden episode of kidney failure or kidney damage that happens within a few hours to days. Non-Steroidal Anti-Inflammatory Drugs and/or acetaminophen are commonly used in mild to moderate pain management. NSAID and/or acetaminophen have been reported to cause reversible acute renal failure. A 68-year-old male patient brought with the chief complaints on admission of vomiting, breathlessness since 4 days, pain in the abdomen since 5 days, burning sensation in chest, burning micturition, haematuria since 2 weeks. He was a known case of wind-swept deformity and receiving combination of Tablet Diclofenac sodium 50 mg/Acetaminophen 500 mg once a day in the past 8 years for knee pain. He was diagnosed with Rapidly Progressive Renal Failure-Acute Kidney Injury, Contrast induced Nephropathy, Bladder Outlet Obstruction. The laboratory investigations show abnormality in the serum creatinine, blood urea, haematological parameters indicate normocytic normochromic anaemia with neutrophilic leucocytosis. In the assessment of this case it was found that Diclofenac/Acetaminophen has induced Rapidly Progressive Renal Failure. After withdrawal of Diclofenac/Acetaminophen all the values returned within the normal range and his oedema was also subsiding, showing clinical improvement with the diuretic treatment, fluid, and salt restriction.
Keywords: Diclofenac; Acetaminophen; Renal Failure; Diuretics; Non-Steroidal Antiinflammatory Drugs; Prostaglandin